Modification Of Natural Rubber Sir-20 With Cyclisation and Grafting Methods with Maleic Anhydride - Eddiyanto Eddiyanto; Andreas Nababan; April Sinaga (Indonesian Journal of Chemical Science and Technology (IJCST), 2022)
Modification  has been carried out through a cyclization process using an organic solvent of Xylene in the various of concentration of P2O5 as a  Lewis Acid catalyst followed by the grafting process of Maleic Anhydride (MA) monomer using dicumyl peroxide (DCP) as the initiator. The success of the cyclization process of CNR formation can be seen from the FTIR analysis which shows typical peaks at the absorption wave of 741 cm-1 from the CH2 – CH2 cyclical strain vibration and a wavelength of 835 cm-1 from the non-cyclical strain vibration CH2 – CH2 indicating that cyclization has occurred. Furthermore, on the results of grafting, FTIR analysis was carried out to prove that the MA had been grafted on the Cyclic Natural rubber (CNR) so that the formation of CNR-g-MA as shown of the C=O wave number which was on wave number 1710 cm-1 and 1850 cm-1.